The Impact of Higher Education in the Economic Development: A Case of Libya - Omar, Ali Salih (2011)
Education is at the crossroads for the future of the Middle East and North Africa (MENA) countries like Libya. It plays a crucial role in promoting poverty alleviation and economic growth, both at national and at household levels. It also reflects the aspirations of the people for a successful integration into the global economy in an ever changing world. This research aimed to recognize the role of higher education in economic development in Libya, so the research problem represented of discovering the relationship between high education and economic development, in addition to stand on the reality of higher education and economic development in Libya. The paper uses an analytical description to meet the research purposes. The findings show that Libya and other MENA countries give large attention to the higher education based on government participation which aimed to pave the ways and techniques responsible for developing the education and enhancing economic development.